Evaluating Time Series Models in Short and Long-Term Forecasting of Canadian Air Passenger Data - Emiray, Emir; Rodriguez, Gabriel (Université d'Ottawa | University of Ottawa, 2003)
This paper uses six time series models to forecast seasonally unadjusted monthly data of Canadian enplaned/deplaned air passengers, for the domestic, transborder and international sectors. We find that forecasting performance of the models varies widely across series and forecast horizons. Our forecasting results are compared with forecasts published by Transport Canada’s Aviation Forecasting Division. / Ce travail utilise six modèles de séries chronologiques afin de prévoir les données mensuelles (sans adjustement saisonniers) des embarquements/atterrissages des passagers aériens canadiens pour les vols domestiques et internationaux. Nous trouvons que la performance dans les prévisions varie grandement selon les séries et selon l’horizon. Nos prévisions sont comparées avec celles publiées par la division des prévisions d’aviation de Transport Canada.
Keywords: Forecasts; Seasonal Unit Roots; ARIMA Models; Periodic Autoregressive Models; Structural Time Series Model; Prévisions; racines unitaires saisonnières; modèle ARIMA; modèles périodiques auto-régressifs; modèles de séries chronologiques structurelles